2022
DOI: 10.1007/s00784-022-04389-x
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose CBCT imaging of alveolar buccal bone adjacent to mandibular anterior teeth— a pilot study

Abstract: Objectives Accurate description of buccal bone adjacent to mandibular anterior teeth is helpful for planning and monitoring periodontal and orthodontic treatment. Low-dose cone beam computed tomography (LD-CBCT) imaging has shown promising results for very small dental structures in animals. This study asserts that LD-CBCT is sufficiently accurate to measure buccal alveolar bone adjacent to human mandibular anterior teeth. Materials and methods Buccal bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Furthermore, creating extensive bone defects and taking multiple intra-oral radiographs and CBCT scans in a patient would be ethically unacceptable. For this reason, the methodology used is justified and in line with other studies [13,14,33].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Furthermore, creating extensive bone defects and taking multiple intra-oral radiographs and CBCT scans in a patient would be ethically unacceptable. For this reason, the methodology used is justified and in line with other studies [13,14,33].…”
Section: Discussionmentioning
confidence: 58%
“…In other words, it is far more likely to underestimate a buccal bone defect using IOR compared to CBCT. One of the only articles that is similar to our research is the paper by Ruetters et al [33]. In this pilot study, a low-dose CBCT was used to evaluate the buccal bone adjacent to the mandibular anterior teeth.…”
Section: Discussionmentioning
confidence: 73%
“…Ruetters et al showed that low-dose CBCT is a precise and reliable method for detecting and measuring furcation defects in mandibular and maxillary molars in an experimental setting. They reported that low-dose CBCT has the potential to improve treatment planning and treatment monitoring, involving a far lower radiation dose than conventional high-dose-CBCT [ 28 ]. Oenning et al (DIMITRA research) demonstrated that it is possible to achieve a good balance between dose and image quality using a small FOV, and even small details can be assessed in likely optimized protocols (e.g., evaluation of lamina dura and periodontal ligament space).…”
Section: Discussionmentioning
confidence: 99%
“…protocol and the Low Dose C.B.C.T. protocol used, ejected a dose (dap 69 and 87 mGycm2) which is lower than that of panoramic views (Dap 88 mGycm2) [10].…”
Section: Introductionmentioning
confidence: 99%
“…systems with low-dose protocols and ultra-low-dose C.B.C.T. are able to determine, with an appropriate diagnostic quality, both the vertical component and the horizontal component of bone, providing and representing an important accurate and reliable method for assessing the bone structure of the anterior area [10].…”
Section: Introductionmentioning
confidence: 99%